Effect of laser-assisted nitriding with a high-power diode laser on surface hardening of aluminum-containing martensitic steel. (August 2019) - Sim, Ahjin; Park, Chankyoo; Kang, Namhyun; Kim, Yangdo; Chun, Eun-Joon
Highlights: Laser nitriding of AISI P21 steel with a high-power diode laser and vacuum chamber. Surface hardness of increased approximately 40% after laser nitriding. Rectangular AlN precipitates were formed within 15 μm depth from the surface after laser nitriding. Increased surface hardness after laser nitriding was attributed to formation of the AlN. Abstract: The surface of steel molds used in injection molding must be particularly hard to withstand abrasive fiber-reinforced plastics. Thus, a laser nitriding process using a gas chamber setup is suggested as a surface modification process for the plastic mold industry in this study. The hardness distributions and microstructural evolution of AISI P21 steel after laser nitriding were fundamentally investigated and compared with the results of laser-assisted selective melting without nitrogen. After laser-assisted selective melting, the hardness had not changed relative to that of the base metal (410 HV), although the martensitic transformation had occurred in the melted zone. On the other hand, the laser-nitrided specimen (at 4500 mm/J of heat input) was approximately 40% (573 HV) harder than the base metal was before laser nitriding. In the region with increased hardness, an area with a high level of nitrogen was observed. In other words, nitrogen successfully penetrated into the surface of the specimen, and it formed a certain layer that corresponded well with the region of increased hardness. Moreover, the microstructure of the nitrogen condensed layer in Al-based nitride (AlN) was characterized by transmission electron microscopy. According to these results, the hardening behavior of AISI P21 steel after laser nitriding was mainly attributed to the development of the AlN phase.